An Efficient Copper‐Catalyzed One‐Pot Synthesis of 1‐Aryl‐1, 2, 3‐triazoles from Arylboronic Acids in Water under Mild Conditions. Issue 11 (13th November 2015) - Hao, Changbo; Zhou, Changjian; Xie, Jianwei; Zhang, Jie; Liu, Ping; Dai, Bin
Abstract: A convenient method for one‐pot two‐step 1, 3‐dipolar cycloadditon reaction of arylboronic acid, sodium azide followed with terminal alkynes in the presence of 2‐pyrrolecarbaldiminato‐Cu(II) complexes catalyst is reported. Various 1‐aryl‐1, 2, 3‐triazoles were prepared in 63%–97% yields in water at 30°C without any additives and avoiding the isolation of unstable aryl azides. Abstract : A new one‐pot two‐step procedure was developed to prepare 1‐aryl‐1, 2, 3‐triazoles in good to excellent yields from arylboronic acids in water under mild and operationally simple conditions.